2017
DOI: 10.18632/oncotarget.15502
|View full text |Cite
|
Sign up to set email alerts
|

Annonaceous acetogenins mediated up-regulation of Notch2 exerts growth inhibition in human gastric cancer cellsin vitro

Abstract: BackgroundGastric cancer (GC) is a global health problem because of limited treatments and poor prognosis. Annonaceous acetogenins (ACGs) has been reported to exert anti-tumorigenic effects in cancer, yet the mechanism underlying its effects on GC remains largely unknown. Notch signaling plays a critical role in cell proliferation, differentiation and apoptosis. Therefore, it may contribute to the development of GC. This study aims to explore the role of Notch2 in ACGs’ activities in GC cells.ResultsACGs inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…GC is one of the most common cancers in China, with high mortality due to its aggressiveness, and poor prognosis (1113). Although a number of genes and signaling pathways involved in GC development have been identified (1417), the mechanism is still too sophisticated to be fully understood. Identifying novel genes closely associated with GC development is clinically necessary.…”
Section: Discussionmentioning
confidence: 99%
“…GC is one of the most common cancers in China, with high mortality due to its aggressiveness, and poor prognosis (1113). Although a number of genes and signaling pathways involved in GC development have been identified (1417), the mechanism is still too sophisticated to be fully understood. Identifying novel genes closely associated with GC development is clinically necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, we also found distinct findings amongst different authors. Inhibition at the G2-M phase was reported by Magadi (20,38,46,49,54,56,58). Neither of these two contrasting observations might be wrong, as they perform different observations in different cell lines.…”
Section: Discussionmentioning
confidence: 94%
“…Convincing evidence indicated that Notch1 and NICD was highly expressed in the AGS cell line ( 10 , 44 ). An additional study indicated that there was no significant difference between the levels of Notch2 in the normal gastric epithelial AGS and GES-1 cell lines ( 45 ). For Notch3 and Notch4, there have been no studies that have observed a difference in Notch3 or Notch4 expression between the AGS cell line and normal gastric cells.…”
Section: Discussionmentioning
confidence: 99%